THE EFFECT OF SINGLE- AND REPEATED- EXCESSIVE SWIMMING EXERCISE ON KIDNEY HISTOPATHOLOGY OF MALE RATS WISTAR STRAIN (Rattus norvegicus) - Tripani, Wenni Juniarni; Ilmiawan, Muhammad In’am; Handoko, Willy (Faculty of Medicine and Health Universitas Muhammadiyah Jakarta, 2020)
Background: Physical exercise aims to improve or maintain physical fitness. However, excessive physical exercise may cause increase of oxidative stress which leads to cellular injury, including in the proximal tubules of kidney. This research aims to find out the effect of single- and repeated- excessive swimming exercise to the kidney histopathology of male wistar rats (Rattus norvegicus). Methods: This research was an experimental study with complete random and post test only control group design. Twenty seven male wistar rats were divided into three treatment groups: control group, single- excessive swimming exercise group (45 minutes for one day), and repeated- excessive swimming exercise group (45 minutes/day for seven days). In the end of the treatment, the kidney of the rats were taken to be analyzed by using hematoxylin-eosin stain. The mean of proximal tubules injury of kidneys were counted by two observers using blinded method. Data were analyzed by using one way anova test. Result: The analysis showed there was a significant difference in the mean percentage of proximal tubules injury between control group and single swimming group as well as the repeated swimming group (Anova p=0,000), also there was significant difference between the treatment groups (p=0,020). The highest average of proximal tubules injury was in the single swimming group. Conclusion: Single- and repeated- excessive swimming exercise causes the proximal tubules injury of kidney.